(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Small scale enterprises are catalyst in achieving nation’s economic objectives, but not without constraints that impede their growth. This paper ascertained the extent bank collateral Security demandon loansaffect thegrowthofsmallscaleenterprisesinOnitsha,Anambra State.Oneresearch question guided the study, while one null hypothesis was tested at 0.05 level of significance. Descriptive survey research design was adopted forthestudyand a population of352 owners ofsmall scale enterprisesin Onitsha,Anambra State was used for the study. Data were collected for the study using validated structured questionnaire on a five -point rating scale. The internal consistency of the instrument yielded an index value of 0.83, which was established with Cronbach Co-efficient Alpha. The findings of the study revealed among others that bank collateral securities demands on loan affected the growth of small scale enterprises at moderate, low and very low extents. However, the study showed that gender did not affect the opinion of the small scale enterprises on the extent collateral security demand affect the growth of their enterprisesin Onitsha, Anambra State. Based on the findings of the study, it was recommended among others that entrepreneurs’ in Onitsha, Anambra State should embark on capacity building of their members to ensure better understanding of financial institutionsrequirementsforloanand thecollateraldemandsonthem.